NEURAL PAIN PATHWAY TRACING OF RABBIT ISCHEMIC HEART BY DOUBLE-RETROGRADE NEUROTRACING - Dapamede, Theodorus; Paundralingga, Obed Trinurcahyo Kinantyo; Rahayu, Masruroh; Soemantri, Bambang (Malang Neurology Journal, 2015)
Background. Myocardial ischaemia leads to angina pectoris or referred pain, whichhappens because of the inability of the brain to distinguish the visceral afferent inputs from the somatic afferent inputs since they run along a common pathway via the dorsal root ganglia.Objective. To distinguish specific areas of the rabbit heart that are projected to specific dorsal root ganglia, which then associates to its specific dermatomes.Methods. A double-retrograde neurotracing method was used, with True Blue and Nuclear Yellow as the neurotracers. Rabbits were divided into 3 groups, which the first and second groups were ligated at the left anterior descending artery and at the left circumflex artery, respectively.The third group acted as the control group, without ligation.Results. There is significant association between the site of ligation to the projection of the neurotracers at specific dorsal root ganglia (p<0.05). The first group showed high tendency to be projected to T2 and the second group showed a high tendency to project to T1.Conclusion. This study shows that the rabbit heart can be specifically projected neuronally to specific dorsal root ganglia, following coronary artery ligation.